2019
DOI: 10.1111/sjop.12593
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing images: The role of motivational significance, complexity, social content, age, and gender

Abstract: Memory for affective events plays an important role in determining people’s behavior and well‐being. Its determinants are far from being completely understood. We investigated how recognition memory for affective pictures depends on pictures’ motivational significance (valence and arousal), complexity (figure‐ground compositions vs. scenes), and social content (pictures with people vs. without people) and on observers’ age and gender. Younger, middle‐aged, and older adults viewed 84 pictures depicting real‐lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 89 publications
(148 reference statements)
0
9
0
Order By: Relevance
“…In one study, women demonstrated better item recognition memory for happy faces, but not neutral or negative faces, in comparison to men (Wang, 2013). Gomez et al (2020) observed greater item recognition memory in women versus men, yet this enhancement was not driven by differences in responding to emotional or social content. Additionally, Naveh-Benjamin et al (2012) found that older women demonstrated better associative recognition memory for emotionally negative images than men, though this effect was not seen in younger adults.…”
Section: Emotional and Social Memorymentioning
confidence: 74%
See 2 more Smart Citations
“…In one study, women demonstrated better item recognition memory for happy faces, but not neutral or negative faces, in comparison to men (Wang, 2013). Gomez et al (2020) observed greater item recognition memory in women versus men, yet this enhancement was not driven by differences in responding to emotional or social content. Additionally, Naveh-Benjamin et al (2012) found that older women demonstrated better associative recognition memory for emotionally negative images than men, though this effect was not seen in younger adults.…”
Section: Emotional and Social Memorymentioning
confidence: 74%
“…These findings suggest that social and emotional cues may exert either reinforcing or competing effects on recognition memory, depending upon the type of memory under investigation, and thus are likely driven by at least partially distinct underlying mechanisms. Finally, prior research has been equivocal regarding gender differences in emotional and social memory (Asperholm et al, 2019;Gomez et al, 2020;Wang, 2013), potentially related to small sample sizes and piecemeal examination of social and emotional effects. Offsetting these limitations, the present study found an enhancement of associative recognition memory performance overall in women compared to men, but no reliable gender differences in item recognition or social or emotional memory performance specifically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study employs one of the largest and most diverse samples to date to examine gender differences in emotional memory and thus may provide a more definitive contribution to the inconsistent findings of this body of work. Notably, most studies that observed null gender effects on item recognition memory also involved larger, more diverse community samples (e.g., Gomez et al, 2020; Naveh-Benjamin et al, 2012; Spalek et al, 2015), whereas studies that have reported significant gender effects primarily involve small samples of undergraduate students (e.g., Cahill & van Stegeren, 2003; Canli et al, 2002). Recent reviews and meta-analyses suggest that women and men tend to be more alike than different across a range of neurocognitive domains (e.g., Asperholm et al, 2020; Hirnstein et al, 2019), and that the small differences observed in memory, when they do occur, may arise from differences in socialization and cultural expectations of men and women rather than innate or biological causes (e.g., caregivers talk about emotions more frequently with girls than with boys; Raval & Walker, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, research suggests social information is more attention grabbing (Thornton & Conway, 2013) though surprisingly less research has explored how social versus nonsocial content is later remembered, especially in the context of emotion. In one study, Gomez and colleagues (2020) found that images containing social information (i.e., images containing people) were better recognized at a later memory test than images with no social information. However, though social images ranged in emotional valence from negative to positive—and negative images were better recognized than neutral images—the authors did not examine potential interactive or additive effects of emotional and social information together.…”
mentioning
confidence: 99%